موقف ابن حزم من المنطق الأرسطي: رؤية علمية: Ibn Hazm’s Position on Aristotelian Logic: A Critical Reading - Mohamed Meerasahibu, Dheen Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Ibn Ḥazm has been among the most vocal supporters of Aristotelian logic, yet enjoys strong sympathies from scholars hostile to logic. This paper is an attempt to harness the sympathies of this group of scholars for Ibn Ḥazm to prompt them to revisit their position of antagonism. In order to achieve this objective, the paper discusses two issues; first, it discusses Ibn Hazm’s essential confidence and defense of Aristotelian logic; at the same time, it addresses his criticism of some of Aristotle’s premises and assumptions without in anyway undermining his deep sense of appreciation for Aristotle. The second issue highlight, through three examples, the shallowness of the accusation – of individuals both in the past and the present –levelled against Ibn Hazm that he, when criticizing Aristotle, displayed ignorance of his ideas. The paper concludes that his criticism depicts a well-informed independent personality with a sound understanding and that there is reason enough for those antagonistic towards logic to start giving serious thought to what Ibn Ḥazm has to offer in this regard.